Provide a four-tier model for feasibility and effective deployment of good governance in higher education - reyhaneh pourhassan; Habibollah Salarzehi; Seyyed Aligholi Roshan; noor mohammad yaghoubi; Masood Dehghani (پژوهش در نظام‌های آموزشی, 2020)
The overall goal of the study was to provide a four-tier model of feasibility and effective deployment of good governance in higher education. The research method of the present study is meta-synthesis and revision of the subject. The findings of relevent qualitative and quantitative research were combined and the present model was designed. A total of 298 articles in the field of good governance in education were evaluated, and at the end, 60 studies were selected and by analyzing their content, the relevant dimensions and codes were extracted and the importance and priority of each was determined using Shannon entropy. The findings showed that the codes for continuous financial reporting, managing the process of change in education and research based on environmental changes, flexibility in law enforcement, the legitimacy of authority, mastery of curriculum, teaching experience, having skilled staff, removing barriers Access to education, efforts to create the right environment for raising public awareness, and coordination among stakeholders among the three dimensions of good governance are most important. The four-step model presented in the present study enables the transition from the current situation to the optimal one for establishing good governance effectively.